Application of linguistic modelling to systems and product design. (5th May 2020) - Korn, Janos
Design thinking is an integral part of problem solving which is an incessant activity in the living sphere for survival and achievement of ambitions, the alternative is extinction. There is a variety of problem solving or design methods usually pursued separately for systems and product in business, management, in engineering and fashion design otherwise the activity is carried out instinctively, it is innate. The aim of this paper is to introduce an integrated design thinking procedure which is supported by the 'new science of systems' in particular by linguistic modelling. Thus, design thinking has acquired a theoretical support with clearly different functions of the systems and component designers. Parts of 'science of systems' relevant to design thinking are described which serve as guidance for design activity. Problematic issues and expectations of those affected can be elucidated by managers, designers and individuals leading to emergence of a scheme intended to aid systemic thinking for solving problems and to detailed design of prototype models while admitting creativity and innovation.